Thrombosis Risk Assessment in Myeloproliferative Neoplasm—Is There a Role for Viscoelastic Testing? - Lim, Hui Yin; Ho, Prahlad (Seminars in Thrombosis and Hemostasis, 2022)
Philadelphia chromosome-negative myeloproliferative neoplasms include polycythemia vera, essential thrombocythemia, and myelofibrosis. They are associated with increased thrombotic events, and the primary goal of therapy, in particular those with polycythemia vera and essential thrombocythemia, is the prevention of thrombotic complications typically with antiplatelet therapy and/or cytoreduction. While several patient-, disease-, and genomic-related factors have been identified to influence thrombotic risks, there are no routine laboratory investigations to date that are sufficiently accurate to assess the underlying procoagulant state and predict the thrombotic risks. Conventional coagulation testing only measures time to clot formation and cannot reliably predict bleeding and thrombotic risks. Global coagulation assays such as thromboelastography, thrombin, and fibrin generation may provide a more thorough assessment of hemostatic function. Thromboelastography and thromboelastometry are viscoelastic tests which measure the mechanical properties of the hemostatic process, including the global dynamics of clot formation, stabilization, and dissolution. While viscoelastic testing is gaining traction in the investigations of coagulopathies and goal-directed blood product replacement in trauma and massive transfusion settings, the role of these assays in thrombosis is less well defined. Here, we provide a review of the current evidence of the role of viscoelastic testing in myeloproliferative neoplasm, particularly in the thrombotic risk assessment.
Keywords: viscoelastic test; thromboelastography; thromboelastometry; thrombosis; myeloproliferative neoplasm